Design of Data Warehouse Technology for Data Performance Management in Universities - Maulidar (Postgraduate, University of Mataram, 2023)
The purpose of this research is Change Management for Organizations to find out change management for organizations and organizational change factors by using the nine steps methodology approach developed by Kimball. The results of this study are that information technology assistance provided by Pelindo I is the right step. Moreover, the scope of the business being managed is so wide, covering ports in the Sumatran archipelago and overseeing thousands of employees. Business process automation is becoming an effective way for companies to force irresistible change. If the rules are written, even though they have been mutually agreed upon, employees can still work around them. But technology can be coercive effectively and can eventually lead to cultural change. Performance management is simply productivity, how can employee productivity be measured based on predetermined targets? MKE Pelindo I with a technology base makes everything completely objective, transparent, and has clear measurements. When each person is competing to make an optimal contribution to the company, at that time all the wheels of the organization will move dynamically. Then based on Kotter's 8-step evaluation, the change process that was carried out for the first time in 2004-2014 which was not conducive was caused by the not forming a strong enough team to direct the process. And this is what creates resistance also from employees. Then it wasn't created at the beginning of creating the right vision, but changes had been implemented, meaning that subordinate employees were invited to change without communicating a vision.